Review of the action of organic matter on mineral sediment flocculation - Deng, Zhirui; Huang, Dong; He, Qing; Chassagne, Claire (Frontiers in Earth Science, 2022)
Sediment is found throughout the world's alluvial plain rivers, estuarine coasts and adjacent seas and is thereby a key factor in major ecosystems. Suspended mineral sediment can affect the biological activity of microorganisms and plants, by reducing light penetration in the water column or by binding to organic matter. Biological processes can, in turn, affect the physical and chemical properties of the sediment particles and influence the adhesion between particles. They can facilitate the sediment aggregation (flocculation) through bridging, patching and sweep, while biological decay will mainly help to disintegrate organic matter rich flocs. Biological activity also affects the properties of flocs (structure, density, sedimentation rate and composition). This activity is itself influenced by environmental conditions (like temperature, light and nutrient fluxes). Sediment flocculation thus involves complex relationships between several physical, chemical and biological factors. The role of biology in particular needs to be better integrated in sediment transport models, through the interaction between mineral clay particles, microorganisms and their excreted polymers (Extra Polymeric Substances, i.e. EPS). In this article, a summary of the state-of-the-art research regarding sediment flocculation is given. In particular, the action of organic matter on fine-grained sediment flocculation is discussed. The aim of the article is to provide a more comprehensive understanding of bio-sediment dynamics and give an outlook on remaining research questions.